A Modified Microscopic-Endoscopic Bilateral Transseptal Approach for Pituitary Adenomas: Comparisons of Nasal Outcome and Quality of Life Using the Microscopic Transnasal Approach - Zhong, Junjie; Gu, Yanfang; Zheng, Jie; Yang, Bojie; Qi, Zengxin; Li, Tianwen; Shen, Chao; Shi, Zhifeng (Frontiers in Oncology, 2022)
Objectives In this study, we introduced a novel modified microscopic-endoscopic bilateral transseptal approach for pituitary adenoma resection to minimize surgery-related nasal injury. We also retrospectively compared comprehensive nasal outcomes and quality of life between the microscopic transnasal approaches. Methods Patients with pituitary adenomas who underwent modified microscopic-endoscopic bilateral transseptal or microscopic transnasal approaches were assessed for olfactory function and quality of life using the Sniffin’ Sticks test, the Sino-Nasal Outcome Test-22 (SNOT-22), the SF-36, the anterior skull base (ASK) nasal inventory, and the subjective visual analog scale (VAS) before and 1 and 3 months after surgery. A nasal endoscopy procedure was also performed to evaluate structure abnormalities at 1 and 3 months after surgery. Results Fifty-eight patients who underwent either modified microscopic-endoscopic bilateral transseptal (35 patients) or microscopic transnasal (23 patients) surgery were consecutively enrolled. Patients who underwent either transnasal approach experienced similar surgical complications, except for intraoperative cerebrospinal fluid leakage (43.5% vs 14.3% for modified microscopic-endoscopic bilateral transseptal or microscopic transnasal approach, respectively; p = 0.013). Patients who underwent the two approaches fully recovered according to the SF-36, SNOT-22, VAS, and Sniffin’ Sticks surveys, but not ASK scores, 3 months post-operatively. There was no significant difference in nasal endoscopy outcome at 3 months follow-up between the two approaches. Conclusions The modified microscopic-endoscopic bilateral transseptal approach showed largely similar nasal mucosa protective outcomes to those of the microscopic transnasal approach for pituitary adenoma surgery. After pituitary adenoma resection using the modified approach, patients’ postoperative olfactory function, nasal structure, and quality of life can be restored to preoperative status within 3 months.